A Novel Technique for Microcatheter Additional Shaping During Intracranial Aneurysmal Coil Embolization: Microcatheter Shaping Cast - Ohshima, Tomotaka (Asian J Neurosurg, 2019)
BACKGROUND: When a shaping mandrel is inserted into the tip of a preshaped microcatheter, the existing curve becomes uncertain because the tip is straightened by the inner mandrel. Therefore, we developed a way to perform microcatheter shaping by means of an external cast, which we named “microcatheter shaping cast.” TECHNIQUES: A shaping mandrel attached to a microcatheter was used and coiled 4–5 times around a metallic introducer, which was attached using a microguidewire. Then, a stent-like handmade cast was prepared. After the microcatheter tip was inserted into the cast, it was manually bent according to the aneurysmal shape and size. The tip and cast were heated with a hot air gun. We evaluated the relationship between degrees of bending and heating time to achieve appropriate right-angled shaping memory. CONCLUSIONS: The presented microcatheter shaping method should be more useful than conventional internal shaping, especially in cases that require an additional microcatheter shaping or reshaping during aneurysmal coil embolization.